Pengaruh Strategi Biaya Rendah dan Diferensiasi terhadap Keberhasilan PT Tahu Tauhid - Vina Merliana; Albert Kurniawan (Universitas Kristen Maranatha, 2016)
This study discusses the company PT TAHU TAUHID Lembang in the city, the researchers are interested in doing research on this company, as the company is one part of the changes to the types of food in the know begin by providing a variety of flavors to him. The factory is well know for success in business, the company's emphasis on increasing the efficiency and utilization of external circumstances, while also maintaining its uniqueness PT TAHU TAUHID. To the authors to take the title of the thesis about Influence Strategies (Low Cost and Differentiation) the success of the business. The purpose of this study was todetermine a low cost to determine the success of PT TAHU TAUHID Lembang, and to determine the differentiation strategy of competitive advantage held by PT TAHU TAUHID Lembang. In the sampling method nonprobability sampling is saturatedwith 75 employees. The results from 75 employees to prove that the competitive advantage of Differentiation shows more influence on the success of its PT TAHU TAUHID, whereas Low cost does not significantly affect the success of PT TAHUTAUHID.Keywords: Strategies Competitive Advantage, Low Cost, Differentiation, The success of the business.